Relationship between Budget Participation, Budget Procedural Fairness, and Department director’s/ Budget manager’s activities: The Study of Asia-Pacific International University - Mom, Rey (Journal of International Scholars Conference - BUSINESS & GOVERNANCE, 2016)
This study investigates the correlation between budget participation, budget procedural fairness, and department director’s/budget manager’s performance at Asia-Pacific International University (AIU). Generally, department directors/budget managers do not seem interested in participating and sharing the important information they have with their supervisor while supervisors also seem uninterested of department director’s/budget manager’s ideas or information while preparing the annual budget. This study is a quantitative research, and a questionnaire was the main instrument for data collection. The questionnaires were distributed to the 38 department directors/budget managers of AIU. Multiple regression and multi correlation were used to test the variables. Overall, the analysis found no positive influence between budget participation and budget procedural fairness on department director’s/budget manager’s activities. Several limitations can be noticed in this study include population collected from only directors or budget managers of a small university. It also used only two variables, budget participation and budget procedural fairness, as an influence on department director’s/budget manager’s activities.